PhosphoGRID: a database of experimentally verified in vivo protein phosphorylation sites from the budding yeast Saccharomyces cerevisiae - Stark, Chris (Oxford University Press, 2010)
Protein phosphorylation plays a central role in cellular regulation. Recent proteomics strategies for identifying phosphopeptides have been developed using the model organism Saccharomyces cerevisiae, and consequently, when combined with studies of individual gene products, the number of reported specific phosphorylation sites for this organism has expanded enormously. In order to systematically document and integrate these various data types, we have developed a database of experimentally verified in vivo phosphorylation sites curated from the S. cerevisiae primary literature. PhosphoGRID (www.phosphogrid.org) records the positions of over 5000 specific phosphorylated residues on 1495 gene products. Nearly 900 phosphorylated residues are reported from detailed studies of individual proteins; these in vivo phosphorylation sites are documented by a hierarchy of experimental evidence codes. Where available for specific sites, we have also noted the relevant protein kinases and/or phosphatases, the specific condition(s) under which phosphorylation occurs, and the effect(s) that phosphorylation has on protein function. The unique features of PhosphoGRID that assign both function and specific physiological conditions to each phosphorylated residue will provide a valuable benchmark for proteome-level studies and will facilitate bioinformatic analysis of cellular signal transduction networks. Database URL: http://phosphogrid.org/